EDUCATION IN A PERSON OF THE MORAL IDEALS OF SOCIETY - Karimova. M. (Galaxy International Interdisciplinary Research Journal, 2022)
The article reveals the main goals of civic education Tasks of civic education The concept of "citizenship" is ambiguous education of the moral ideals of society in a person education of the moral ideals of society in a person Formation of patriotic feelings and consciousness Formation of patriotic feelings and consciousness Formation of ecological culture The system of methods and forms of formation of citizenship of the individual .